(untitled) (ENTHYMEMA, 2019)
From October 23 to 26 of last year eminent scholars, specialists of Dostoevsky, met in Sofia for the «International Symposium: Dostoevsky’s Anthropology. The man as a problem and object of representation in the world of Dostoevsky», a conference organized at Sofia University “St. Kliment Ohridski” by the Bulgarian Dostoevsky Society and by the Institut for Literature of the Bulgarian Academy of Sciences.